Análise do perfil dos empreendedores e caracterização dos empreendimentos do centro comercial de Marcelino Vieira/RN - Cardozo, Janne Mary Alves (Universidade Federal Rural do Semi-Árido, 2020)
In importance to the great growth of entrepreneurs in Brazil, it is essential to analyze and characterize the entrepreneurs in the cities. Capitalist society is going through a new era, where individuals feel the need to take initiatives as a way of adapting to the environment in which they are inserted, changing lifestyles, habits, work environments and even transforming something simple into more sophisticated ones, causing the community to need this new product or service offered. This phenomenon, known as entrepreneurship, is increasingly visible on the world market, transforming low-income people into small, medium and even large entrepreneurs, due to a simple idea in which they are improving with acquired experiences and knowledge. , making them great entrepreneurs. This work has as main objective the visualization of this phenomenon in the Northeast Region, specifically in the semi-arid hinterland in the city of Marcelino Vieira – RN. For the construction of this work, a bibliographic-documental research was used as methodology, through the classic literature and a field research, in addition to the case study. Thus, a form was applied, which sought to analyze the distribution by gender, the distribution according to the age group in the enterprises, the education level of the entrepreneurs, the age of the companies, and their distribution according to the sectors of the economy, as well such as the use of information technologies available on the market.
Monografia
Keywords: Empreendedorismo; Inovação; Empreendedores; Entrepreneurship; Innovation; Entrepreneurs; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA